Optimalisasi Pengelolaan Dana Ziswaf dalam Meningkatkan Kesejahteraan Ekonomi Anggota Koperasi Syari’ah Benteng Mikro Indonesia Cabang Cikupa, Tanggerang - Suardi, Didi; Abdul Hafidz, Jafar (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2021)
This study aims to understand the ZISWAF fund management strategy carried out by the Benteng Mikro Indonesia Sharia Cooperative (BMI) Cikupa Tangerang Branch in improving welfare for members and non-members. Research at the location was motivated by the success of the cooperative in making efforts to optimize it, even that success was not only felt by cooperative members, non-members also felt. This success has inspired researchers to go directly to the field, see and ask questions about the ZIZWAF fund management strategy in depth. This is because researchers have observed that various zakat fund management has not been maximized, some are stagnant, some are declining and not developing. So it is necessary to look for zakat management formulations that have been proven to be optimal. For this reason, this study uses qualitative analysis methods with data collection techniques through observation, in-depth interviews, and documentation. The random sampling technique is random sampling. The determination of the sampling technique or informant depends on the topic and the objectives of the research itself. The results show that in terms of the management of Islamic cooperatives, BMI has planned programs to improve the economic welfare of members and non-members of the branch of the BMI Islamic cooperative. Cikupa. However, the impact is still not felt by members and non-members because it is not in accordance with their needs. However, the BMI sharia cooperative has a Ready-to-Live Home Grant (HRSH) program, this program is very helpful for members and non-members who do not have a house or have a house that is not suitable for habitation.